Identification of Conflict Resolution in Civil Relations between Boarding House Owners and Boarding House Residents (Study at Semarang State University Campus Circle) - Rio Taufik Ansori; Saniya Puspitasari; Vira Azra; Tegar Islami Putra; Aprila Niravita (Universitas Negeri Semarang, 2023)
This study aims to investigate conflict resolution between residents and boarding house owners in civil relations near the Semarang State University campus. Utilizing a mixed-methods approach, combining normative juridical research with empirical field data, the research discovered that the majority of conflicts are resolved through non-litigious channels. The legal framework for out-of-court settlements aligns with Law No. 30 of 1999 on Alternative Dispute Resolution. Notably, the civil relationship dynamics around the UNNES campus involve a lease agreement between property owners and tenants, whether formalized in writing or conveyed orally. The study sheds light on the prevalence of non-litigation methods in resolving conflicts, emphasizing the significance of alternative dispute resolution mechanisms. This research contributes valuable insights into the legal aspects of the landlord-tenant relationship, providing a nuanced understanding of the complexities in civil relations within the context of university campus housing.